2010
DOI: 10.1037/a0018599
|View full text |Cite
|
Sign up to set email alerts
|

Strategy selection and use during classification skill acquisition.

Abstract: Two experiments examined 3 variables affecting accuracy, response time, and reports of strategy use in a binary classification skill task. In Experiment 1, higher rule cue salience, allowing faster rule application, produced higher aggregate rule use than lower rule cue salience. After participants were pretrained on the relevant classification rule, rule reports were high but generally declined across training trials; after participants were pretrained on an irrelevant rule, reports of the relevant rule incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
1
39
1
Order By: Relevance
“…Bourne et al also manipulated the presence of novel items during training, and reported retrieval use for repeated items was lower for participants who were also presented with novel items than for participants who were not presented with novel items. Bourne et al (2010) offered an interesting explanation for their results that contrasts sharply with current instance-based theories of automaticity. According to Bourne et al, learners compare the costs and benefits of both the algorithmic process and the retrieval process.…”
Section: Evidence For Control Of Retrievalcontrasting
confidence: 49%
See 3 more Smart Citations
“…Bourne et al also manipulated the presence of novel items during training, and reported retrieval use for repeated items was lower for participants who were also presented with novel items than for participants who were not presented with novel items. Bourne et al (2010) offered an interesting explanation for their results that contrasts sharply with current instance-based theories of automaticity. According to Bourne et al, learners compare the costs and benefits of both the algorithmic process and the retrieval process.…”
Section: Evidence For Control Of Retrievalcontrasting
confidence: 49%
“…Although Bourne et al (2010) attributed their results to controlled use of retrieval based on cost-benefit comparisons, instance-based theories of automaticity may still account for their results without the assumption of control. To revisit, instance-based theories of automaticity state that the likelihood of retrieval depends on the relative speed at which retrieval versus the algorithm can be completed.…”
Section: Evidence For Control Of Retrievalmentioning
confidence: 86%
See 2 more Smart Citations
“…Multiple laboratory studies have confirmed this shift over a variety of arithmetic and nonarithmetic tasks (Delaney, Reder, Staszewski & Ritter, 1998;Hertzog, Touron & Hines, 2007;Jenkins & Hoyer, 2000;Logan, 1988Logan, , 1992Onyper, Hoyer & Cerella, 2006;Palmeri, 1997;Rawson, 2004;Reder & Ritter, 1992;Rickard, 1997Rickard, , 1999Rickard, , 2004Rickard & Bajic, 2003Rogers, Hertzog & Fisk, 2000;Schunn, Reder, Nhouyvanisvong, Richards & Stroffolino, 1997;Touron, Hoyer & Cerella, 2001). An understanding of the temporal dynamics of strategy execution in these tasks is integral to the broader goal of modeling the underlying learning processes and performance mechanisms, as well as the factors that may modulate the rate of the strategy shift (e.g., Bourne, Raymond & Healy, 2010;Onyper et al, 2006;Salvucci & Taatgen, 2008;Touron & Hertzog, 2009).…”
mentioning
confidence: 99%